Utilizing Google Classroom; Voices of an English Teacher and Students from a Senior High School English in Jambi - Muncar Winarti; Amalia Nurhasanah; Rumiati Ningsih (ELITE JOURNAL, 2020)
The paper aims at uncovering the lived experience of a senior high school English teacher after utilizing Google Classroom as a digital teaching tool during the pandemic era, in the last semester of the academic year 2019-2020. This study was a descriptive qualitative inquiry. The researchers did an in-depth interview and participatory observation to gather the data. The participants of this study were an English teacher and students from a State Senior High School 4 Tebo in Jambi Province Indonesia. The findings reveal the benefits and lack of Google Classroom for both students and teachers. Indeed, Google Classroom proposed a brand-new way of transferring English material to students from which they felt joy and facilitated to learn English. However, the quality of internet connections and time allotment of each meeting brought about weaknesses since the teacher was lacking time to accommodate all topics during the semester.